2016
DOI: 10.1515/psicl-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Simplification in inter- and intralingual translation – combining corpus linguistics, key logging and eye-tracking

Abstract: AbstractAs some scholars view inter-and intra-lingual translation as a parallel activity, it is vital to establish to what extent the products of these processes are alike, and whether the processes themselves differ. This paper investigates stylistic simplification, a frequently hypothesised translation universal which involves, among others, breaking up long sentences in the process of translation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Based on this comparative approach, several empirical-experimental studies have been carried out to reveal how far paraphrase overlaps with translation in terms of process and products. Kajzer-Wietrzny et al [24] combined corpus linguistics, key-logging and eye-tracking to investigate whether stylistic simplification, a frequently hypothesized indicator of translation universal, was equally present in the end products of paraphrase and translation and how this tendency was related to the level of translation expertise. Whyatt et al [25] reported a comparative study of decision-making process in paraphrase and translation by collecting user activity data (UAD) via key-logging, eye-tracking and screen recording.…”
Section: Cognitive Explorations Of Translation and Paraphrasementioning
confidence: 99%
See 3 more Smart Citations
“…Based on this comparative approach, several empirical-experimental studies have been carried out to reveal how far paraphrase overlaps with translation in terms of process and products. Kajzer-Wietrzny et al [24] combined corpus linguistics, key-logging and eye-tracking to investigate whether stylistic simplification, a frequently hypothesized indicator of translation universal, was equally present in the end products of paraphrase and translation and how this tendency was related to the level of translation expertise. Whyatt et al [25] reported a comparative study of decision-making process in paraphrase and translation by collecting user activity data (UAD) via key-logging, eye-tracking and screen recording.…”
Section: Cognitive Explorations Of Translation and Paraphrasementioning
confidence: 99%
“…First, eye movement measures need be enriched in reflect multiple dimensions of processing. For instance, Kajzer-Wietrzny et al [24] merely used dwell time to indicate the cognitive effort allocated to different textual regions. It is essential to further exploit the advantage of eye-tracking in recording and describing cognitive behaviors by adopting eye movement measures reflective of not only overall cognitive effort but also attention dividing mechanism.…”
Section: Cognitive Explorations Of Translation and Paraphrasementioning
confidence: 99%
See 2 more Smart Citations
“…health domain experts), who are therefore involved in the workflow of intralingual translation (i.e. simplification of content to render it accessible to lay readers) (Muñoz-Miquel 2012;Kajzer-Wietrzny, Whyatt, and Stachowiak 2016). Different sets of written guidelines are available to the authors of PLS, which deal with both content (e.g.…”
Section: The Case Of Cochranementioning
confidence: 99%